End-to-end modelling and performance analysis for network virtualisation in the next generation internet. (1st January 2012) - Duan, Qiang
Coordinating heterogeneous networking systems to meet diverse application requirements has become a significant issue in the future internet. Network virtualisation provides a promising approach to solving this problem. Understanding the end-to-end service performance in future internet is a significant opening topic, which requires modelling and analysis on service provisioning in network virtualisation. Network heterogeneity and resource abstraction in network virtualisation bring new challenges on service modelling and analysis. The research presented in this paper addresses these challenges. The main contributions made in this paper include a new model for end-to-end network service delivery systems in network virtualisation environments, and the techniques for analysing end-to-end performance of service delivery in the virtualisation-based internet. The model and techniques developed in this paper are general and independent of network architectures and implementation technologies; therefore can be applied to analyse the performance of various heterogeneous networking systems converged in the next generation internet.